Knowledge, awareness, and practices of menstrual cup usage among Malaysia’s undergraduate students - Law, Yoo Kee; Fong, Chng Saun; Chin, Kim Ling (Penerbit Universiti Kebangsaan Malaysia, 2025)
This study explores undergraduate students' knowledge, awareness, and practices toward menstrual cups, highlighting key factors influencing their adoption and continued use. Despite growing awareness, sustained usage remains low due to significant barriers, including concerns about comfort, safety and insufficient information. Utilizing a survey approach, this study examines the motivations and challenges associated with menstrual cup adoption, as well as the role of different information sources. The study underscores the importance of menstrual health education, considering variables like environmental impact awareness and economic factors. Understanding university students' perspectives on menstrual cups is crucial for designing effective education programs. The discussion section critically examines safety concerns and the impact of awareness campaigns. It emphasizes the necessity of targeted educational initiatives to address knowledge gaps and promote positive discussions around menstrual cups. The study concludes by discussing the implications of encouraging sustainable menstrual hygiene practices and empowering the younger generation to make informed choices for their well-being and the environment.